Studies on the Chemical Forms of Urinary Lead. Issue 2 (April 1960) - Dinischiotu, G. T.; Nestorescu, B.; Radulescu, I. C.; Ionescu, C.; Preda, N.; Ilutza, G.
Abstract : Lead in urine has been determined by an ashing technique to give total lead and by a standard coprecipitation technique to give precipitable lead. In 44 normal subjects values obtained by both methods were the same. In 72 subjects exposed to lead, of whom 57 had clinical lead poisoning, the precipitable lead was significantly less than the total lead. As much as 40% of urinary lead can escape determination by the coprecipitation methods of estimation. Preliminary findings suggest that the non-precipitable lead may be present as a natural chelate. The significance of these observations is discussed. The danger is stressed that cases of threatened lead intoxication may be overlooked if only coprecipitation methods of estimating lead in urine are used.